Comparison of the Efficacy of Intravenous Lignocaine and Intravenous Dexmedetomidine in Attenuation of Hemodynamic Stress Response to Laryngoscopy and Endotracheal Intubation - Nand, Raja; Feroz, Shizan Hamid; Ahmed, Mirza Sijeel; Jafri, Syed Asad Ullah; Sultan, Muhsan; Ahmed, Niaz (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the effect of intravenous Lignocaine and Dexmedetomidine to attenuate cardiovascular stress reaction to laryngeal manipulation. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Anesthesia, Combined Military Hospital, Peshawar Pakistan, from Oct 2019 to Apr 2020. Methodology: Patients were randomly divided into two Groups by lottery method. Seventy-three were in the intravenous Lignocaine-Group-(A), while 73 patients were in the intravenous Dexmedetomidine-Group-(B). Blood pressure, Pulse rate and ECG were documented at the start of general anaesthesia and after 1, 3 and 5 minutes of intubation. Efficacy was defined if systolic pressure and pulse remained within 20% of the patient’s native findings between 1 and 5 minutes after endotracheal intubation. Results: A total of 146 patients were included in the stud. The mean baseline systolic BP of Group-A was 121.34±4.47mmHg and mean baseline diastolic BP was 80.31±3.57mmHg. While mean Baseline Systolic BP WAS 121.19±4.37mmHg in Group-B and mean baseline diastolic BP was 80.04±3.66mmHg. Efficacy was seen 74% patients of Group-A and 90.4% of Group-B (p=0.009). Conclusion: Dexmedetomidine 1 microgram/kg blunts the cardiovascular sympathetic reaction to laryngeal manipulation more pronounced than Lignocaine 1.5 milligram/kg without any harmful outcomes.